Growth-response variation among selected coliform isolates under antibiotic stress in the Brantas River, East Java, Indonesia - RIDWAN MUHAMAD RIFAI; CAMAR AMERIL; BAKHRUL MUKHID FADILAH RAMADANI; LUTHFIYA ANNAILAH; ANIE YULISTYORINI (Society for Indonesian Biodiversity, 2026)
Abstract. Rifai RM, Ameril C, Ramadani BMF, Annailah L, Yulistyorini A. 2026. Growth-response variation among selected coliform isolates under antibiotic stress in the Brantas River, East Java, Indonesia. Biodiversitas 27 (6): d270615. https://doi.org/10.13057/biodiv/d270615. Domestic wastewater inputs can influence microbial diversity and Anti-Microbial Resistance (AMR) in river systems. However, growth-response diversity among AMR-related coliform isolates remains poorly characterized. This is particularly relevant in the upper Brantas, where millions of people live in its watershed. Most previous assessments have focused on endpoint susceptibility profiles, while temporal growth responses under increasing antibiotic exposure remain less explored. In this study, coliform bacteria were isolated from a single densely populated riverbank site in the upper Brantas River. Selected isolates were tentatively identified as Escherichia coli, Klebsiella aerogenes, Klebsiella variicola, and Klebsiella pneumoniae. All Klebsiella isolates were resistant to amoxicillin, and K. aerogenes also showed resistance to tetracycline. We performed growth assays using antibiotic levels based on the Clinical and Laboratory Standards Institute (CLSI) breakpoints. Klebsiella aerogenes maintained growth up to 4× CLSI breakpoint. At the same time, K. variicola and K. pneumoniae grew more slowly and showed biphasic patterns, whereas E. coli was entirely suppressed. These findings remind us that even isolates from the same river site and with similar susceptibility classifications can respond differently when exposed to antibiotics. Growth-response profiling adds valuable insights beyond standard susceptibility tests and can help us better understand the phenotypic diversity within environmental AMR reservoirs. To deepen our understanding, future research should include larger collections of isolates, samples from multiple locations, and molecular studies to uncover the mechanisms behind these varied responses.